EFFECTIVENESS OF NEEM OIL (Azadirachta indica) AS AN ANTIBACTERIAL AGENT TOWARDS DENTAL CARIES BACTERIA ( Streptococcus mutans ) - Vithya Lakshmi Bjya Gabal; Angga Prawita Kautsar (Farmaka, 2017)
ABSTRACT One of the usual oral disease in the world is dental caries. It is normally triggered by the microorganisms Streptococcus mutans. Where tooth enamel will be affected. Regardless of the fact that poor hygiene and interrelated to multiple full-body conditions and diseases are one of the major cause that around 80% of all over the world adults will be identified with caries. As number carries cases increase but there are only a few successful preventative treatments. Herbal treatment research towards bacterial ecology in the mouth and the other correlated factors that may contribute to caries are being carried out. The awareness of new treatment and prevention options for this exceedingly usual infection are being figured out. One of effective treatment is Neem (Azadirachta indica) as antibacterial, antifungal, and biopesticide. Most recent research is towards the effectiveness of neem oil towardsStreptococcus mutans as antibacterial due to its active properties. Keywords : Dental caries, Streptococcus mutans, Neem oil, Antibacterial activity.